Soft magnetic composite material and preparation method and application thereof
By covering three layers of insulating layers on the magnetic powder core of the soft magnetic composite material, the problems of high-frequency eddy current loss and poor thermal stability of the insulating layer are solved, and excellent magnetic performance and high-frequency stability are achieved.
Patent Information
- Application Number
- CN202510050226.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-01
AI Technical Summary
The eddy current loss of existing soft magnetic composite materials increases dramatically under high-frequency conditions, which limits its application range. The thermal stability and brittleness of the insulating coating materials are poor, and they are prone to rupture during compaction.
A mixture of carbonyl iron powder and FeSiMoV amorphous powder is coated as the magnetic powder core, and three insulating layers are sequentially coated on its surface: the first layer is a phosphorus-based coating layer grown in situ, the second layer is an organic resin coating layer, and the third layer is an inorganic oxide coating layer.
It significantly reduces the eddy current loss of soft magnetic composite materials under high frequency conditions, improves magnetic performance and thermal stability, and avoids the cracking of the insulating layer during the pressing process.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of soft magnetic materials, and in particular to a soft magnetic composite material and a preparation method and application thereof. Background Art
[0002] Soft magnetic materials refer to materials that are easier to magnetize and demagnetize and have high initial magnetic permeability. m i , low coercivity H c And high saturation magnetization M s . Soft magnetic materials are widely used in the cores of transformers, inductors, reactors, relays and ballasts, etc. They are important functional materials in the fields of electrical engineering, radio, communications, etc. Soft magnetic materials can be mainly divided into three categories: soft magnetic metal alloys, ferrite soft magnetic materials and soft magnetic composite materials. Among them, soft magnetic composite materials are mainly magnetic materials prepared by mixing metal magnetic powder particles with insulating materials and combining annealing process. They are widely used in electronic components such as inductors, filters, choke coils, etc. The demand for soft magnetic composite materials for electronic components in the fields of communications, computers and new energy vehicles is also increasing. However, the sharp increase in eddy current loss under high frequency conditions greatly limits its application at high frequencies.
[0003] In the prior art, the eddy current loss between particles and within particles is reduced mainly by effectively insulating the surface of the alloy powder and selecting the ratio of the powder particle size. However, the particle size of the powder has a direct impact on the density, magnetic permeability and loss of the soft magnetic composite material. Therefore, choosing a suitable particle size distribution and particle size ratio is crucial to improving the overall magnetic properties of the material, which requires a lot of time and cost. Therefore, at present, more people are developing insulating coating materials with high resistivity to suppress eddy current losses.
[0004] According to the type of coating material, it is mainly divided into inorganic coating and organic coating, but organic coating materials usually have poor thermal stability, and inorganic coating materials are prone to cracking during compaction, resulting in a significant increase in high-frequency eddy current loss. Based on this, the development of a soft magnetic composite material that can effectively suppress high-frequency eddy current loss is of great practical significance for improving the magnetic properties of soft magnetic materials. Summary of the invention
[0005] In view of the problem that the insulating coating materials in the prior art have poor thermal stability and are prone to cracking during the compaction process, resulting in a substantial increase in high-frequency eddy current losses, the present invention provides a soft magnetic composite material and its preparation method and application. The soft magnetic composite material is a mixture of carbonyl iron powder and FeSiMoV amorphous powder as a magnetic powder core, and three insulating layers are sequentially coated on its surface, wherein the first insulating layer is an in-situ grown phosphorus-based coating layer; the second insulating layer is an organic coating insulating layer; and the third insulating layer is an inorganic oxide coating layer. The soft magnetic composite material provided by the present invention has excellent magnetic properties and low eddy current losses under high-frequency conditions, and has good thermal stability. It is not easy to crack during the pressing process, which provides a new design idea for the preparation of soft magnetic composite materials.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The first aspect of the present invention provides a soft magnetic composite material, which includes a powder core and a first insulating layer and a second insulating layer sequentially coated on the surface of the powder core from the inside to the outside; wherein the powder core is a mixture of phosphate-coated carbonyl iron powder and phosphate-coated FeSiMoV amorphous powder; the first insulating layer is an organic resin coating layer; and the second insulating layer is a transition metal oxide layer.
[0007] Compared with the prior art, the present invention selects a mixture of phosphate-coated carbonyl iron powder and phosphate-coated FeSiMoV amorphous powder as the powder core of the soft magnetic composite material. Carbonyl iron powder has high saturation magnetization, low coercive force, good thermal conductivity and good high-frequency adaptability, but the activity of carbonyl iron powder is relatively large. After phosphate coating, it not only retains its good magnetic properties, but also further improves its stability. FeSiMoV amorphous powder is added with Mo and V elements on the basis of FeSi alloy. The addition of Mo element can significantly enhance the passivation film stability of FeSiMoV amorphous material and improve the corrosion resistance of the alloy, while the addition of V element can significantly increase the resistivity of FeSiMoV amorphous material, and can also improve the morphology of the alloy, making it easier to spheroidize. In addition, the addition of V can also reduce the powder voids of the magnetic powder core during the preparation process, increase the density of the magnetic powder core, and thus improve the magnetic properties of the soft magnetic composite material. The FeSiMoV amorphous powder coated with phosphate can remove the non-magnetic oxide layer on the surface of the amorphous particles, achieving an insulating coating effect, thereby improving the resistivity and effective magnetic permeability of the soft magnetic composite material. The present invention mixes phosphate-coated carbonyl iron powder with phosphate-coated FeSiMoV amorphous powder, and effectively improves the filling factor and magnetic permeability of the magnetic powder core through a reasonable ratio.
[0008] The present invention also designs two layers of insulating coating, the first layer is an organic resin coating layer, and the second layer is a transition metal oxide layer. The organic resin coating can make up for the defect of large brittleness of the inorganic coating layer, and avoid the problem of cracking of the insulating layer caused by subsequent pressing. At the same time, the transition metal oxide layer can improve the problem of poor thermal stability of the organic resin coating layer. The combination of organic coating and inorganic coating can not only provide sufficient mechanical strength for the soft magnetic composite material, but also achieve the purpose of improving the magnetic properties of the soft magnetic composite material and reducing eddy current loss. The present invention adopts two layers of insulating coating, which not only improves the insulation effect, reduces eddy current loss, and improves high-frequency stability, so that the obtained soft magnetic composite material can still maintain low loss under high-frequency conditions, and improves the performance of the soft magnetic composite material as a whole.
[0009] Preferably, the particle size of the phosphate-coated carbonyl iron powder is 50 μm-100 μm.
[0010] Preferably, the particle size of the phosphate-coated FeSiMoV amorphous powder is 10 μm-30 μm.
[0011] Preferably, the mass ratio of the phosphate-coated carbonyl iron powder to the phosphate-coated FeSiMoV amorphous powder is 0.3:1-0.5:1.
[0012] Preferably, the FeSiMoV amorphous powder in the phosphate-coated FeSiMoV amorphous powder comprises the following components in percentage by mass: Si: 8.7%-9.2%, Mo: 3.2%-3.7%, V: 1.8%-2.4% and the balance Fe.
[0013] Preferably, the raw materials of the organic resin coating layer are polyamide resin and epoxy resin in a mass ratio of 1:2-1:3.
[0014] Preferably, the raw material of the transition metal oxide layer is manganese dioxide.
[0015] Preferably, the thickness of the first insulating layer is 50nm-100nm.
[0016] Preferably, the thickness of the second insulating layer is 100 nm-250 nm.
[0017] The second aspect of the present invention provides a method for preparing the soft magnetic composite material, comprising the following steps: Step 1: Fe powder, Si powder, Mo powder and V powder are weighed according to the designed ratio, mixed evenly, and powdered by gas atomization in an inert atmosphere, and sieved to obtain FeSiMoV amorphous powder; Step 2, mixing the carbonyl iron powder and the FeSiMoV amorphous powder, ball milling and annealing to obtain a mixed powder; Step 3, dispersing the powder core raw material in a phosphate acetone solution, performing a coating treatment at 25°C-60°C, and drying; performing a high temperature treatment to obtain a mixed coated powder; adding an adhesive curing agent to the mixed coated powder, granulating, curing, and sieving to obtain a powder core raw material; Step 4: Disperse the powder core raw material in the alcohol solution of the mixed resin, stir evenly, perform a primary insulation coating treatment at 75° C.-90° C., and dry to obtain a primary insulation coating material; ball mill the primary insulation coating material and manganese dioxide powder for 10 h-15 h, perform a secondary high-temperature treatment, and obtain a secondary insulation coating material; Step 5: Press the secondary insulating coating material into a shape to obtain a ring-shaped sample; heat the ring-shaped sample to 400° C.-550° C. in an inert atmosphere to obtain a soft magnetic composite material.
[0018] The present invention first anneals the alloy powder, and uses high temperature to eliminate the internal stress between the alloy powders, thereby avoiding cracking caused by the large internal stress of the powder core during the subsequent pressing process. The present invention also adds two high-temperature treatments during the coating process, and uses multiple high-temperature treatments to make the coating layer more compact and improve the magnetic properties of the soft magnetic composite material. The organic resin coating layer can not only serve as an insulating coating layer, but also as a bonding layer to firmly agglomerate the inorganic oxide layer and the phosphate-coated magnetic powder core raw materials together, so that the soft magnetic composite material has higher mechanical properties.
[0019] Preferably, in step 1, the temperature of the atomization method is 1850°C-2000°C.
[0020] Preferably, in step 2, the rotation speed of the ball mill is 800 rpm-1000 rpm, and the time of the ball mill is 2 h-3 h.
[0021] Preferably, in step 2, the temperature of the annealing treatment is 650° C.-800° C., and the holding time of the annealing treatment is 1 h-2 h.
[0022] Further preferably, in step 2, the temperature is raised to 650°C-800°C by programmed heating, and the heating rate is 10°C / min-20°C / min.
[0023] Preferably, in step three, the mass concentration of phosphoric acid in the acetone phosphate solution is 1%-3%.
[0024] Preferably, in step three, the temperature of the high temperature treatment is 200°C-300°C, and the time of the high temperature treatment is 30min-50min.
[0025] In step three, the adhesive curing agent is epoxy resin, polyether amine and alicyclic amine in a mass ratio of 1:1:0.5-1:1:0.8.
[0026] In step three, the particle size of the powder core raw material is 70 μm-100 μm.
[0027] In step three, the amount of the adhesive curing agent added is 25%-35% of the mass of the mixed coated powder.
[0028] Preferably, in step 4, the volume ratio of the mixed resin to the alcohol solution in the mixed resin alcohol solution is 1:1-1:1.2, and the alcohol solution is 70wt%-80wt% ethanol solution.
[0029] Preferably, in step 4, the temperature of the secondary high temperature treatment is 250°C-350°C, and the time of the secondary high temperature treatment is 2h-4h.
[0030] Preferably, in step three or step four, the drying temperature is 90° C.-140° C., and the drying time is 10 h-14 h.
[0031] Preferably, in step five, the unidirectional pressing pressure of the pressing molding is 750MPa-850MPa, and the holding time of the pressing molding is 15s-20s.
[0032] Preferably, in step five, the heat treatment is carried out at a holding time of 3 h to 5 h.
[0033] Further preferably, in step five, the temperature is raised to 400°C-550°C by programmed heating, and the heating rate is 5°C / min-15°C / min.
[0034] The third aspect of the present invention provides the use of the soft magnetic composite material in the preparation of power electronic equipment and components.
[0035] In summary, the present invention provides a soft magnetic composite material, which uses a mixture of phosphate-coated carbonyl iron powder and phosphate-coated FeSiMoV amorphous powder as a magnetic powder core, and two insulating layers are sequentially coated on the surface thereof; wherein the first insulating layer is an organic resin-coated insulating layer; and the second insulating layer is a manganese dioxide coating layer. By utilizing the interaction of each component, the soft magnetic composite material has excellent magnetic properties and low eddy current loss under high-frequency conditions, and has good thermal stability and is not prone to cracking during the pressing process. The technical solution of the present invention effectively solves the problem in the prior art that the insulating coating material has poor thermal stability and is prone to cracking during the compaction process, resulting in a substantial increase in high-frequency eddy current losses, and provides a new design idea for the preparation of soft magnetic composite materials. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Example 1 This embodiment provides a soft magnetic composite material, which specifically includes the following contents: The soft magnetic composite material comprises a powder core and a first insulating layer and a second insulating layer sequentially coated on the surface of the powder core from the inside to the outside; wherein the powder core is a phosphate-coated carbonyl iron powder and a phosphate-coated Fe 85.3 Si9Mo 3.5 V 2.2 A mixture of amorphous powders, wherein the particle size of the phosphate-coated carbonyl iron powder is 80 μm; the phosphate-coated Fe 85.3 Si9Mo 3.5 V 2.2 The particle size of amorphous powder is 20 μm; The first insulating layer is a 60nm thick organic resin coating layer; the second insulating layer is a 200nm thick manganese dioxide layer.
[0038] The preparation method of the soft magnetic composite material comprises the following steps: Step 1: Weigh Fe powder, Si powder, Mo powder and V powder according to the designed ratio, mix them evenly, put them into a vacuum atomization furnace, set the temperature to 1950℃, heat for 3h, and use gas atomization method to make powder in an inert atmosphere to obtain Fe 86.3 Si8Mo 3.5 V 2.2 Amorphous powder; Step 2: Mix 4g of carbonyl iron powder and 10g of Fe 85.3 Si9Mo 3.5 V 2.2 The amorphous powders were mixed uniformly, ball-milled at a rotation speed of 900 rpm for 2.5 h, and the ball-milled raw materials were heated to 750° C. at a heating rate of 15° C. / min and annealed for 1.5 h to obtain mixed powders; Step 3, dispersing the mixed powder in 20mL of 2wt% acetone phosphate solution, coating at 45°C, and drying at 120°C for 10h; high-temperature treating the dried material at 250°C for 40min to obtain a mixed coated powder; adding 30wt% of an adhesive curing agent to the mixed coated powder, granulating, curing, and passing through a 150-mesh sieve to obtain a powder core raw material; wherein the adhesive curing agent is an epoxy resin, a polyether amine, and an alicyclic amine in a mass ratio of 1:1:0.6; Step 4: Disperse the powder core raw material in 25 mL of an alcohol solution of a mixed resin, stir evenly, perform an insulating coating treatment at 85°C, and dry at 100°C for 10 hours to obtain a primary insulating coating material; ball-mill the primary insulating coating material and 45 g of manganese dioxide powder for 12 hours, heat the temperature to 300°C for a secondary high-temperature treatment for 3 hours to obtain a secondary insulating coating material; wherein the mixed resin is a polyamide resin and an epoxy resin in a mass ratio of 1:3; the volume ratio of the mixed resin to a 75wt% ethanol solution is 1:1.
[0039] Step 4: Press the secondary insulating coating material into shape, set the unidirectional pressing pressure to 800 MPa, press for 15 seconds, and obtain a ring-shaped sample; in an inert atmosphere, heat the ring-shaped sample to 500°C at a heating rate of 10°C / min for 4 hours to obtain a soft magnetic composite material.
[0040] Example 2 This embodiment provides a soft magnetic composite material, which specifically includes the following contents: The soft magnetic composite material comprises a powder core and a first insulating layer and a second insulating layer sequentially coated on the surface of the powder core from the inside to the outside; wherein the powder core is a phosphate-coated carbonyl iron powder and a phosphate-coated Fe 85.7 Si 8.7 Mo 3.2 V 2.4 A mixture of amorphous powders, wherein the particle size of the phosphate-coated carbonyl iron powder is 60 μm; the phosphate-coated Fe 85.7 Si 8.7 Mo 3.2 V 2.4 The particle size of amorphous powder is 10 μm; The first insulating layer is a 95nm thick organic resin coating layer; the second insulating layer is a 250nm thick manganese dioxide layer.
[0041] The preparation method of the soft magnetic composite material comprises the following steps: Step 1: Weigh Fe powder, Si powder, Mo powder and V powder according to the designed ratio, mix them evenly, put them into a vacuum atomization furnace, set the temperature to 2000℃, heat for 3h, and use gas atomization method to make powder in an inert atmosphere to obtain Fe 85.7 Si 8.7 Mo 3.2 V 2.4 Amorphous powder; Step 2: Mix 4g of carbonyl iron powder and 10g of Fe 85.7 Si 8.7 Mo 3.2 V 2.4The amorphous powders were mixed uniformly, ball-milled at a speed of 800 rpm for 3 h, and the ball-milled raw materials were heated to 800 °C at a heating rate of 20 °C / min for annealing for 1.5 h to obtain mixed powders; Step 3, dispersing the mixed powder in 20mL of 1.5wt% acetone phosphate solution, coating at 60°C, and drying at 120°C for 10h; high-temperature treating the dried material at 300°C for 40min to obtain a mixed coated powder; adding 35wt% of an adhesive curing agent to the mixed coated powder, granulating, curing, and passing through a 200-mesh sieve to obtain a powder core raw material; wherein the adhesive curing agent is an epoxy resin, a polyether amine, and an alicyclic amine in a mass ratio of 1:1:0.5; Step 4: Disperse the powder core raw material in 25 mL of an alcohol solution of a mixed resin, stir evenly, perform an insulating coating treatment at 85°C, and dry at 100°C for 10 hours to obtain a primary insulating coating material; ball-mill the primary insulating coating material and 45 g of manganese dioxide powder for 12 hours, heat the temperature to 300°C for a secondary high-temperature treatment for 3 hours to obtain a secondary insulating coating material; wherein the mixed resin is a polyamide resin and an epoxy resin in a mass ratio of 1:3; the volume ratio of the mixed resin to a 75wt% ethanol solution is 1:1.
[0042] Step 4: Press the secondary insulating coating material into shape, set the unidirectional pressing pressure to 800 MPa, press for 15 seconds, and obtain a ring-shaped sample; in an inert atmosphere, heat the ring-shaped sample to 450°C at a heating rate of 15°C / min for 4 hours to obtain a soft magnetic composite material.
[0043] Example 3 This embodiment provides a soft magnetic composite material, which specifically includes the following contents: The soft magnetic composite material comprises a powder core and a first insulating layer and a second insulating layer sequentially coated on the surface of the powder core from the inside to the outside; wherein the powder core is a phosphate-coated carbonyl iron powder and a phosphate-coated Fe 85.3 Si 9.2 Mo 3.7 V 1.8 A mixture of amorphous powders, wherein the particle size of the phosphate-coated carbonyl iron powder is 80 μm; the phosphate-coated Fe 85.3 Si 9.2 Mo 3.7 V 1.8 The particle size of amorphous powder is 20 μm; The first insulating layer is a 60nm thick organic resin coating layer; the second insulating layer is a 200nm thick manganese dioxide layer.
[0044] The preparation method of the soft magnetic composite material comprises the following steps: Step 1: Weigh Fe powder, Si powder, Mo powder and V powder according to the designed ratio, mix them evenly, put them into a vacuum atomization furnace, set the temperature to 1950℃, heat for 3h, and use gas atomization method to make powder in an inert atmosphere to obtain Fe 86.3 Si8Mo 3.5 V 2.2 Amorphous powder; Step 2: Mix 4g of carbonyl iron powder and 10g of Fe 85.3 Si9Mo 3.5 V 2.2 The amorphous powders were mixed uniformly, ball-milled at a rotation speed of 900 rpm for 2.5 h, and the ball-milled raw materials were heated to 750° C. at a heating rate of 15° C. / min and annealed for 1.5 h to obtain mixed powders; Step 3, dispersing the mixed powder in 20mL of 2wt% acetone phosphate solution, coating at 45°C, and drying at 120°C for 10h; high-temperature treating the dried material at 250°C for 40min to obtain a mixed coated powder; adding 30wt% of an adhesive curing agent to the mixed coated powder, granulating, curing, and passing through a 150-mesh sieve to obtain a powder core raw material; wherein the adhesive curing agent is an epoxy resin, a polyether amine, and an alicyclic amine in a mass ratio of 1:1:0.6; Step 4: Disperse the powder core raw material in 25 mL of an alcohol solution of a mixed resin, stir evenly, perform an insulating coating treatment at 85° C., and dry at 100° C. for 10 hours to obtain a primary insulating coating material; ball-mill the primary insulating coating material and 45 g of manganese dioxide powder for 12 hours, heat the temperature to 350° C. and perform a secondary high-temperature treatment for 3 hours to obtain a secondary insulating coating material; wherein the mixed resin is a polyamide resin and an epoxy resin in a mass ratio of 1:3; the volume ratio of the mixed resin to a 75wt% ethanol solution is 1:1.
[0045] Step 4: Press the secondary insulating coating material into shape, set the uniaxial pressing pressure to 800 MPa, press for 15 seconds, and obtain a ring-shaped sample; in an inert atmosphere, heat the ring-shaped sample to 400°C at a heating rate of 5°C / min for 5 hours to obtain a soft magnetic composite material. Comparative Example 1 This comparative example provides a soft magnetic composite material, which is different from Example 1 in that: the powder core is phosphate-coated Fe 85.3 Si9Mo 3.5 V 2.2 Amorphous powder, other ingredients and processes remain unchanged, specifically including the following: The soft magnetic composite material comprises a powder core and a first insulating layer and a second insulating layer sequentially coated on the surface of the powder core from the inside to the outside; wherein the powder core is a phosphate-coated Fe 85.3 Si9Mo 3.5 V 2.2 Amorphous powder; The first insulating layer is a 60nm thick organic resin coating layer; the second insulating layer is a 200nm thick manganese dioxide layer.
[0046] The preparation method of the soft magnetic composite material comprises the following steps: Step 1: Weigh Fe powder, Si powder, Mo powder and V powder according to the designed ratio, mix them evenly, put them into a vacuum atomization furnace, set the temperature to 1950℃, heat for 3h, and use gas atomization method to make powder in an inert atmosphere to obtain Fe 86.3 Si8Mo 3.5 V 2.2 Amorphous powder; Step 2: 10g of Fe 85.3 Si9Mo 3.5 V 2.2 The amorphous powders were mixed uniformly, ball-milled at a rotation speed of 900 rpm for 2.5 h, and the ball-milled raw materials were heated to 750° C. at a heating rate of 15° C. / min and annealed for 1.5 h to obtain powder raw materials; Step 3, dispersing the powder raw material in 20mL of 2wt% acetone phosphate solution, performing a coating treatment at 45°C, and drying at 120°C for 10h; performing a high-temperature treatment at 250°C for 40min after drying to obtain coated powder; adding 30wt% of an adhesive curing agent to the coated powder, granulating, curing, and passing through a 150-mesh sieve to obtain a powder core raw material; wherein the adhesive curing agent is an epoxy resin, a polyether amine, and an alicyclic amine in a mass ratio of 1:1:0.6; Step 4: Disperse the powder core raw material in 25 mL of an alcohol solution of a mixed resin, stir evenly, perform an insulating coating treatment at 85°C, and dry at 100°C for 10 hours to obtain a primary insulating coating material; ball-mill the primary insulating coating material and 45 g of manganese dioxide powder for 12 hours, heat the temperature to 300°C for a secondary high-temperature treatment for 3 hours to obtain a secondary insulating coating material; wherein the mixed resin is a polyamide resin and an epoxy resin in a mass ratio of 1:3; the volume ratio of the mixed resin to a 75wt% ethanol solution is 1:1.
[0047] Step 4: Press the secondary insulating coating material into shape, set the unidirectional pressing pressure to 800 MPa, press for 15 seconds, and obtain a ring-shaped sample; in an inert atmosphere, heat the ring-shaped sample to 500°C at a heating rate of 10°C / min for 4 hours to obtain a soft magnetic composite material.
[0048] Comparative Example 2 This comparative example provides a soft magnetic composite material, which is different from Example 1 in that the powder core is carbonyl iron powder and Fe 86.3 Si8Mo 3.5 V 2.2 The mixture of amorphous powder, other ingredients and processes remain unchanged, specifically includes the following: The soft magnetic composite material comprises a powder core and a first insulating layer and a second insulating layer sequentially coated on the surface of the powder core from the inside to the outside; wherein the powder core is carbonyl iron powder and Fe 85.3 Si9Mo 3.5 V 2.2 A mixture of amorphous powders, wherein the particle size of the carbonyl iron powder is 80 μm; the Fe 85.3 Si9Mo 3.5 V 2.2 The particle size of amorphous powder is 20 μm; The first insulating layer is a 60nm thick organic resin coating layer; the second insulating layer is a 200nm thick manganese dioxide layer.
[0049] The preparation method of the soft magnetic composite material comprises the following steps: Step 1: Weigh Fe powder, Si powder, Mo powder and V powder according to the designed ratio, mix them evenly, put them into a vacuum atomization furnace, set the temperature to 1950℃, heat for 3h, and use gas atomization method to make powder in an inert atmosphere to obtain Fe 86.3 Si8Mo 3.5 V 2.2 Amorphous powder; Step 2: Mix 4g of carbonyl iron powder and 10g of Fe 85.3 Si9Mo 3.5 V 2.2 The amorphous powders were mixed uniformly, ball-milled at a rotation speed of 900 rpm for 2.5 h, and the ball-milled raw materials were heated to 750° C. at a heating rate of 15° C. / min and annealed for 1.5 h to obtain mixed powders; Step 3: adding 30 wt% of an adhesive curing agent to the mixed powder, granulating, curing, and passing through a 150-mesh sieve to obtain a powder core raw material; wherein the adhesive curing agent is an epoxy resin, a polyether amine, and an alicyclic amine in a mass ratio of 1:1:0.6; Step 4: Disperse the powder core raw material in 25 mL of an alcohol solution of a mixed resin, stir evenly, perform an insulating coating treatment at 85°C, and dry at 100°C for 10 hours to obtain a primary insulating coating material; ball-mill the primary insulating coating material and 45 g of manganese dioxide powder for 12 hours, heat the temperature to 300°C for a secondary high-temperature treatment for 3 hours to obtain a secondary insulating coating material; wherein the mixed resin is a polyamide resin and an epoxy resin in a mass ratio of 1:3; the volume ratio of the mixed resin to a 75wt% ethanol solution is 1:1.
[0050] Step 4: Press the secondary insulating coating material into shape, set the unidirectional pressing pressure to 800 MPa, press for 15 seconds, and obtain a ring-shaped sample; in an inert atmosphere, heat the ring-shaped sample to 500°C at a heating rate of 10°C / min for 4 hours to obtain a soft magnetic composite material.
[0051] Comparative Example 3 This comparative example provides a soft magnetic composite material, which is different from Example 1 in that the third insulating layer is an aluminum oxide layer, and other components and processes remain unchanged, specifically including the following contents: The soft magnetic composite material comprises a powder core and a first insulating layer and a second insulating layer sequentially coated on the surface of the powder core from the inside to the outside; wherein the powder core is a phosphate-coated carbonyl iron powder and a phosphate-coated Fe 85.3 Si9Mo 3.5 V 2.2 A mixture of amorphous powders, wherein the particle size of the phosphate-coated carbonyl iron powder is 80 μm; the phosphate-coated Fe 85.3 Si9Mo 3.5 V 2.2 The particle size of amorphous powder is 20 μm; The first insulating layer is a 60nm thick organic resin coating layer; the second insulating layer is a 200nm thick aluminum oxide layer.
[0052] The preparation method of the soft magnetic composite material comprises the following steps: Step 1: Weigh Fe powder, Si powder, Mo powder and V powder according to the designed ratio, mix them evenly, put them into a vacuum atomization furnace, set the temperature to 1950℃, heat for 3h, and use gas atomization method to make powder in an inert atmosphere to obtain Fe 86.3 Si8Mo 3.5 V 2.2 Amorphous powder; Step 2: Mix 4g of carbonyl iron powder and 10g of Fe 85.3 Si9Mo 3.5 V 2.2The amorphous powders were mixed uniformly, ball-milled at a rotation speed of 900 rpm for 2.5 h, and the ball-milled raw materials were heated to 750° C. at a heating rate of 15° C. / min and annealed for 1.5 h to obtain mixed powders; Step 3, dispersing the mixed powder in 20mL of 2wt% acetone phosphate solution, coating at 45°C, and drying at 120°C for 10h; high-temperature treating the dried material at 250°C for 40min to obtain a mixed coated powder; adding 30wt% of an adhesive curing agent to the mixed coated powder, granulating, curing, and passing through a 150-mesh sieve to obtain a powder core raw material; wherein the adhesive curing agent is an epoxy resin, a polyether amine, and an alicyclic amine in a mass ratio of 1:1:0.6; Step 4: Disperse the powder core raw material in 25 mL of an alcohol solution of a mixed resin, stir evenly, perform an insulating coating treatment at 85°C, and dry at 100°C for 10 hours to obtain a primary insulating coating material; ball-mill the primary insulating coating material with 45 g of alumina powder for 12 hours, heat to 300°C for a secondary high-temperature treatment for 3 hours to obtain a secondary insulating coating material; wherein the mixed resin is a polyamide resin and an epoxy resin in a mass ratio of 1:3; the volume ratio of the mixed resin to a 75wt% ethanol solution is 1:1.
[0053] Step 4: Press the secondary insulating coating material into shape, set the unidirectional pressing pressure to 800 MPa, press for 15 seconds, and obtain a ring-shaped sample; in an inert atmosphere, heat the ring-shaped sample to 500°C at a heating rate of 10°C / min for 4 hours to obtain a soft magnetic composite material.
[0054] Comparative Example 4 This comparative example provides a soft magnetic composite material, which is different from Example 1 in that: no high temperature treatment is performed once in step 3, and no secondary high temperature treatment is performed in step 4, and specifically includes the following contents: The soft magnetic composite material comprises a powder core and a first insulating layer and a second insulating layer sequentially coated on the surface of the powder core from the inside to the outside; wherein the powder core is a phosphate-coated carbonyl iron powder and a phosphate-coated Fe 85.3 Si9Mo 3.5 V 2.2 A mixture of amorphous powders, wherein the particle size of the phosphate-coated carbonyl iron powder is 80 μm; the phosphate-coated Fe 85.3 Si9Mo 3.5 V 2.2 The particle size of amorphous powder is 20 μm; The first insulating layer is a 60nm thick organic resin coating layer; the second insulating layer is a 200nm thick manganese dioxide layer.
[0055] The preparation method of the soft magnetic composite material comprises the following steps: Step 1: Weigh Fe powder, Si powder, Mo powder and V powder according to the designed ratio, mix them evenly, put them into a vacuum atomization furnace, set the temperature to 1950℃, heat for 3h, and use gas atomization method to make powder in an inert atmosphere to obtain Fe 86.3 Si8Mo 3.5 V 2.2 Amorphous powder; Step 2: Mix 4g of carbonyl iron powder and 10g of Fe 85.3 Si9Mo 3.5 V 2.2 The amorphous powders were mixed uniformly, ball-milled at a rotation speed of 900 rpm for 2.5 h, and the ball-milled raw materials were heated to 750° C. at a heating rate of 15° C. / min and annealed for 1.5 h to obtain mixed powders; Step 3, dispersing the mixed powder in 20mL of 2wt% acetone phosphate solution, performing a coating treatment at 45°C, and drying at 120°C for 10h; obtaining a mixed coated powder; adding 30wt% of an adhesive curing agent to the mixed coated powder, granulating, curing, and passing through a 150-mesh sieve to obtain a powder core raw material; wherein the adhesive curing agent is an epoxy resin, a polyether amine, and an alicyclic amine in a mass ratio of 1:1:0.6; Step 4: Disperse the powder core raw material in 25 mL of an alcohol solution of a mixed resin, stir evenly, perform an insulating coating treatment at 85° C., and dry at 100° C. for 10 hours to obtain a primary insulating coating material; ball-mill the primary insulating coating material with 45 g of manganese dioxide powder for 12 hours to obtain a secondary insulating coating material; wherein the mixed resin is a polyamide resin and an epoxy resin in a mass ratio of 1:3; the volume ratio of the mixed resin to a 75wt% ethanol solution is 1:1.
[0056] Step 4: Press the secondary insulating coating material into shape, set the unidirectional pressing pressure to 800 MPa, press for 15 seconds, and obtain a ring-shaped sample; in an inert atmosphere, heat the ring-shaped sample to 500°C at a heating rate of 10°C / min for 4 hours to obtain a soft magnetic composite material.
[0057] In order to further reflect the technical effect of the present invention, the present invention conducted the following tests on the soft magnetic composite materials obtained in Example 1 and Comparative Examples 1-4: the saturation magnetic induction intensity Bs of the soft magnetic composite samples was tested using a Hall effect instrument, and the effective magnetic permeability μ of the soft magnetic composite samples at 1 kHz was tested using an impedance analyzer. r , the results are shown in Table 1; The loss of soft magnetic composite materials at different frequencies was tested by BH tester. max=1T; at 1000Hz, B max =0.5T; 50kHz-1000kHz, B max =50mT, the results are shown in Table 2.
[0058] Table 1 Performance test of soft magnetic composite materials obtained in Example 1 and Comparative Examples 1-4
[0059] Table 2 Loss test of soft magnetic composite materials obtained in Example 1 and Comparative Examples 1-4 at different frequencies
[0060] According to Table 1 and Table 2, it can be seen that, compared with Comparative Examples 1-4, the soft magnetic composite material provided in Example 1 of the present invention has higher saturation magnetic induction intensity and higher effective magnetic permeability, and smaller eddy current loss at different frequencies. In particular, the eddy current loss at high frequency (1000kHz) is only 1968.37W / cm 3 , while the soft magnetic composite material described in Comparative Example 1 is as high as 2562.29 W / cm 3 The soft magnetic composite material of Comparative Example 2 is as high as 2311.72W / cm 3 The soft magnetic composite material of comparative example 3 is as high as 2142.75W / cm 3 The soft magnetic composite material of comparative example 4 is as high as 2214.66W / cm 3 It can be seen that the soft magnetic composite material prepared by the technical solution of the present invention can still maintain low eddy current loss under high frequency conditions, effectively solving the problem of high high-frequency eddy current loss of soft magnetic composite materials in the prior art, and providing a new idea for the development of soft magnetic composite materials.
[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A soft magnetic composite material, characterized in that: The soft magnetic composite material comprises a powder core and a first insulating layer and a second insulating layer sequentially coated on the surface of the powder core from the inside to the outside; wherein the powder core is a mixture of phosphate-coated carbonyl iron powder and phosphate-coated FeSiMoV amorphous powder; the first insulating layer is an organic resin coating layer; and the second insulating layer is a transition metal oxide layer.
2. The soft magnetic composite material according to claim 1, characterized in that: The particle size of the phosphate-coated carbonyl iron powder is 50 μm-100 μm; and / or The particle size of the phosphate-coated FeSiMoV amorphous powder is 10 μm-30 μm; and / or The mass ratio of the phosphate-coated carbonyl iron powder to the phosphate-coated FeSiMoV amorphous powder is 0.3:1-0.5:
1.
3. The soft magnetic composite material according to claim 1 or 2, characterized in that: The FeSiMoV amorphous powder in the phosphate-coated FeSiMoV amorphous powder includes the following components in percentage by mass: Si: 8.7%-9.2%, Mo: 3.2%-3.7%, V: 1.8%-2.4% and the balance Fe.
4. The soft magnetic composite material according to claim 1, characterized in that: The raw materials of the organic resin coating layer are polyamide resin and epoxy resin in a mass ratio of 1:2-1:3; and / or The raw material of the transition metal oxide layer is manganese dioxide.
5. The soft magnetic composite material according to claim 1, characterized in that: The thickness of the first insulating layer is 50nm-100nm; and / or The thickness of the second insulating layer is 100nm-250nm.
6. A method for preparing the soft magnetic composite material according to any one of claims 1 to 5, characterized in that: The steps include: Step 1: Fe powder, Si powder, Mo powder and V powder are weighed according to the designed ratio, mixed evenly, and powdered by gas atomization in an inert atmosphere, and sieved to obtain FeSiMoV amorphous powder; Step 2, mixing the carbonyl iron powder and the FeSiMoV amorphous powder, ball milling and annealing to obtain a mixed powder; Step 3, dispersing the mixed powder in a phosphate acetone solution, performing a coating treatment at 25°C-60°C, and drying; performing a high temperature treatment to obtain a mixed coated powder; adding an adhesive curing agent to the mixed coated powder, granulating, curing, and sieving to obtain a powder core raw material; Step 4: Disperse the powder core raw material in the alcohol solution of the mixed resin, stir evenly, perform a primary insulation coating treatment at 75° C.-90° C., and dry to obtain a primary insulation coating material; ball mill the primary insulation coating material and manganese dioxide powder for 10 h-15 h, perform a secondary high-temperature treatment, and obtain a secondary insulation coating material; Step 5: Press the secondary insulating coating material into a shape to obtain a ring-shaped sample; heat the ring-shaped sample to 400° C.-550° C. in an inert atmosphere to obtain a soft magnetic composite material.
7. The method for preparing the soft magnetic composite material according to claim 6, characterized in that: In step 1, the temperature of the gas atomization method is 1850°C-2000°C.
8. The method for preparing the soft magnetic composite material according to claim 6, characterized in that: In step 2, the ball milling speed is 800 rpm-1000 rpm, and the ball milling time is 2 h-3 h; and / or In step 2, the temperature of the annealing treatment is 650° C.-800° C., and the holding time of the annealing treatment is 1 h-2 h.
9. The method for preparing the soft magnetic composite material according to claim 6, characterized in that: In step 3, the mass concentration of phosphoric acid in the acetone phosphate solution is 1%-3%; and / or In step 3, the temperature of the first high temperature treatment is 200°C-300°C, and the time of the first high temperature treatment is 30min-50min; and / or In step 3, the adhesive curing agent is epoxy resin, polyether amine and alicyclic amine in a mass ratio of 1:1:0.5-1:1:0.8; and / or In step 3, the particle size of the powder core raw material is 70 μm-100 μm; and / or In step three, the amount of the adhesive curing agent added is 25%-35% of the mass of the mixed coated powder.
10. The method for preparing the soft magnetic composite material according to claim 6, characterized in that: In step 4, the volume ratio of the mixed resin to the alcohol solution in the mixed resin alcohol solution is 1:1-1:1.2, and the alcohol solution is 70wt%-80wt% ethanol solution; and / or In step 4, the temperature of the secondary high temperature treatment is 250°C-350°C, and the time of the secondary high temperature treatment is 2h-4h.
11. The method for preparing the soft magnetic composite material according to claim 6, characterized in that: In step 5, the unidirectional pressing pressure of the pressing molding is 750MPa-850MPa, and the holding time of the pressing molding is 15s-20s; and / or In step 5, the heat treatment is carried out for a holding time of 3 h to 5 h.
12. Use of the soft magnetic composite material according to any one of claims 1 to 5 in the preparation of power electronic equipment and components.